Hydrodynamic Equilibrium of Teeth Sustentation - José, Ricardo Kina; Kina, (Journal of Dentistry And Oral Implants, 2019)
The article discusses biomechanical principles underlying tooth support and hydrodynamic equilibrium. It considers periodontal ligament behavior, load distribution, and fluid dynamics, linking basic science concepts to clinical implications.
Keywords: periodontal ligament